Ruthenium brachytherapy for uveal melanoma – single institution experience - Rospond-Kubiak, Iwona; Wróblewska-Zierhoffer, Marta; Twardosz-Pawlik, Hanna; Kocięcki, Jarosław (Journal of Contemporary Brachytherapy, 2017)
Purpose : The aim of this study was to report on results of uveal melanoma treatment with ruthenium-106 ( 106 Ru) brachytherapy with long-term follow-up, in terms of local tumor control, eye retention rate, radiation retinopathy, and patients’ survival. Material and methods : Medical records of patients treated with ruthenium plaque due to uveal melanoma at the Department of Ophthalmology, Poznan University of Medical Sciences, Poland, between 1994 and 2014 were retrospectively reviewed. Results : We identified 126 patients: 53 men, 73 women, mean age 60.04 years (range, 21-89). The largest basal diameter ranged from 4.04 mm to 18.9 mm (median, 10.67 mm), tumor height was 1.9 mm to 7.42 mm (median, 4.8 mm). Median scleral radiation dose was 570 Gy (range, 235-1,500 Gy), median apical dose 100 Gy (range, 60-129 Gy). Median follow-up was 66.5 months (range, 2-261 months). We noted a total of 19 (15%) recurrences. The actuarial rate of recurrence was 9.5% at 3 years, and 13.5% at 5 years postoperatively. Nine (7%) eye globes were lost, median time to enucleation was 5 years. The eye retention rate at 5 years was 92.7% and 81% at 10 years. Forty-three (34%) patients died before the end of the study, 24 (19%) of them due to metastatic disease. Metastatic death was related to: tumor size and TNM stage at presentation (p = 0.002 vs. p = 0.0006, respectively) but not to age, gender, and plaque dosimetry. Conclusions : 106 Ru brachytherapy is an effective, globe sparing treatment that provides good tumor control and a high rate of survival. However, some ocular complications tend to appear late post-treatment, and therefore long-term follow-up is advised.